Prediction of Foetal Well-being with Non-stress Test (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Introduction: Non-stress test (NST) is the most common antenatal test performed to assess the foetus at risk of intrauterine hypoxia. On the other hand non-reactivity detected by NST increases the interferences of pregnancy by Caesarean section.Methodology: A cross sectional descriptive study was carried out in the department of Obstetrics and Gynaecology at Dhaka National Medical College between July2007 and June 2008.Objectives: The objectives of the study were (1) To observe the mode of delivery in cases of non-reactive non stress test (NST) and (2) To evaluate perinatal outcome of non-reactive NST.Results: A total 137 high risk pregnant women were included in the study. Age of the women ranges from 16 to 32 years. The mean age of the women was 23.74 ± 3.71 year. Among them 44.53% were primaegravida and 55.47% were multigravida. Gestational age was between 35 and 42 weeks and mean gestational age was 38.34±1.42 weeks. Regarding foetal reactivity 61.3% (n=84) were reactive and 38.7 % (n=53) were non-reactive. Among the babies of non reactive NST 98.11% and 1.89% were delivered by caesarean section and vaginal delivery respectively. Whereas, 48.81% and 51.19% babies of reactive NST were delivered by caesarean section and vaginal delivery respectively. The percentage of caesarean section was much higher in non-reactive NST cases in comparison to that of reactive NST which was statistically highly significant (p value 0.0000). One minute after birth APGAR scoring revealed that 56.6% and 43.4% newborn of non-reactive NST had no depression( APGAR score 7-10) and mild depression ( APGAR score 4-6) respectively. On the other hand 65.47% and 34.5% newborn of reactive NST had no depression and mild depression respectively at one minute after birth. Therefore, small difference was noticed in the neonatal status between the reactive and non-reactive NST which had no statistical significance (p value 0.507). Evaluation of the neonates with APGAR scoring done 5 minutes after birth revealed mild depression (APGAR score 4-6) in 24.53% and 20.24% of non-reactive and reactive NST cases respectively and no depression (APGAR score 7- 10) was found in 75.47% and 70.76% in reactive and nonreactive NST respectively. So, 5 minutes after birth the neonatal status among reactive and non-reactive NST made no significant difference (p value 0.9266).Conclusion: Neonatal evaluation revealed that all foetuses were not compromised as detected by NST. Relying on NST the rate of Caesarean section has been increased. Reassessment of the foetal conditions was needed with the help of other techniques. Therefore NST alone is insufficiently predictive of neonatal outcome.J Bangladesh Coll Phys Surg 2015; 33(2): 65-69